Urban Broadband Internet Policies in Europe: A Critical Review - Willem van Winden; Paulus Woets (European Regional Science Association (ERSA), 2003)
In this paper, urban broadband policies are critically reviewed. Cities and regions in Europe play an increasingly active role in the provision of broadband electronic infrastructure. Some cities are concerned that weaker groups will have little chances to get broadband access, and should be helped. Others take a more offensive stance, and promote broadband access to strengthen the local image, attract innovative companies and/or highly-skilled people. Peripheral cities take action to tackle spatial discrimination by telecom companies. There is now a scientific and political debate as to whether, and to what extent, governments should intervene in broadband markets. Several studies have pointed at the many pitfalls and negative side effects of broadband policies; others are more moderate, or even argue that governments should intervene to prevent a broadband divide. Much of this literature addresses national policies. In this article, we focus on the local level, as local policymakers seem to become more active. In this paper, we present a typology of local/regional broadband policies, based on a number of examples from European cities. We discuss the pro's and cons of various types of intervention, confront the case studies with the arguments listed in the literature, and critically evaluate the policies. Among other things, we conclude that policies are too easiliy justified with "loose" arguments of economic and social benefits, and that too often, policymakers fail to take a technology and supplier neutral approach, which may have perverse impacts in the long run.
Keywords: 330